Research on the Influencing Factors of College Students' Deep Meaningful Learning in Blended Learning Mode - Li, Shu; Pasawano, Tiamyod; Sangsawang, Thosporn (Bright Publisher, 2024)
This study examines the factors that impact deep and meaningful learning in blended learning environments and their connections. The sample included 397 college students from a university in Sichuan Province, selected through random sampling. Data was collected using a questionnaire based on Bandura's ternary interaction theory, encompassing learners, helpers, environment, and interaction dimensions. The following text should be remembered: